1999
DOI: 10.1136/pgmj.75.887.537
|View full text |Cite
|
Sign up to set email alerts
|

Medical restrictions to driving: the awareness of patients and doctors

Abstract: SummaryThe study was set up to investigate the awareness of elderly patients and medical doctors of medical restrictions to driving. Separate questionnaires were completed by patients and doctors. All were interviewed face-to-face, without prior warning and their immediate answers were recorded. In total, 150 elderly patients from the acute elderly care wards, rehabilitation wards and day hospital, and 50 doctors (including all grades from consultant to junior house oYcer) were interviewed. The main outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 9 publications
1
42
1
Order By: Relevance
“…Editor —Kelly et al 's study of knowledge of medical restrictions on driving reveals worrying deficits in doctors' knowledge 1. This accords with results of previous studies2 concerning knowledge of psychiatrists, but contrasts with a comparable study of knowledge3 after dissemination of the Driving Vehicle Licence Authority's (DVLA) “at a glance guidelines” 4…”
mentioning
confidence: 85%
“…Editor —Kelly et al 's study of knowledge of medical restrictions on driving reveals worrying deficits in doctors' knowledge 1. This accords with results of previous studies2 concerning knowledge of psychiatrists, but contrasts with a comparable study of knowledge3 after dissemination of the Driving Vehicle Licence Authority's (DVLA) “at a glance guidelines” 4…”
mentioning
confidence: 85%
“…Other barriers to physician engagement include the lack of physician knowledge on reporting Downloaded by [Baskent Universitesi] at 11:05 21 December 2014 policies and procedures (Cable Reisner, Gerges, and Thirumavalavan, 2000;Gillespie and McMurdo, 1999;Kelly, Warke, and Steele, 1999;Marshall and Gilbert, 1999), statutory protection for physician reporting, as well as the absence of valid and reliable in-office assessment tools.…”
Section: Fatality Crash Rates Of Drivers and Passengersmentioning
confidence: 98%
“…A study in 1996 of GPs referring patients to syncope clinics showed them to be unclear about their responsibilities: only 13% of syncope patients were questioned on their driving by their doctor (MacMahon et al 1996). A study in 1999 in Northern Ireland also demonstrated low awareness; of 50 GPs (2%), one doctor was aware of the availability of the UK Driver & Vehicle Licensing Agency (DVLA) guidelines, 14% (7) could not answer the question, and the remaining 84% (42) gave a range of responses, including contacting the police and the British National Formulary (Kelly et al 1999). Nearly 25% of the 1,000 Canadian physicians in another survey were not aware of the Canadian Medical Association handbook Determining Medical Fitness to Drive: A Guide for Physicians (Jang et al 2007).…”
Section: Introductionmentioning
confidence: 94%